Экономическое неравенство и дистрибутивная парадигма международного антидискриминационного права - Дрёмина-Волок, Наталья Викторовна; Дрьоміна-Волок, Наталія Вікторівна; Drjomina-Volok, Natal'ja (My University, 2011)
The doctrinal foundation and maintenance of the distributive paradigm within the international anti-discrimination law are approached in the article. The concepts of equality of opportunity and equality of results and their implementation in the international antidiscrimination law are examined, and the notion of distributive discrimination is formulated.
Дрёмина-Волок Н. В. Экономическое неравенство и дистрибутивная парадигма международного антидискриминационного права / Н. В. Дрёмина-Волок // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 202-217.
Keywords: дистрибутивная справедливость; международное антидискриминационное право; равенство возможностей; равенство результатов; дистрибутивная дискриминация; дистрибутивна справедливість; міжнародне антидискримінаційне право; рівність можливостей; рівність результатів; дистрибутивна дискримінація; distributive justice; international anti-discrimination Law; equality of opportunity; equality of results; distributive discrimination